2010
DOI: 10.1105/tpc.109.071167
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis of Sulfur-Deprived Chlamydomonas Cells Reveals Aspects of Acclimation Critical for Cell Survival

Abstract: The Chlamydomonas reinhardtii transcriptome was characterized from nutrient-replete and sulfur-depleted wild-type and snrk2.1 mutant cells. This mutant is null for the regulatory Ser-Thr kinase SNRK2.1, which is required for acclimation of the alga to sulfur deprivation. The transcriptome analyses used microarray hybridization and RNA-seq technology. Quantitative RT-PCR evaluation of the results obtained by these techniques showed that RNA-seq reports a larger dynamic range of expression levels than do microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
288
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(309 citation statements)
references
References 117 publications
(150 reference statements)
17
288
4
Order By: Relevance
“…However, focus on the latter has been largely motivated by the renewed interest in microalgae as biofuel feedstocks (Wijffels and Barbosa, 2010). As sequencing technology has become increasingly fast and affordable, comparison of transcriptomic changes under different experimental conditions by massive parallel sequencing of cDNA libraries is a viable first approach toward identifying genes that define changes in response to N deprivation or other nutrient stresses (González-Ballester et al, 2010). With the goal of gaining a better understanding of the factors underlying or even controlling the process of TAG accumulation following N deprivation, the focus has to be on metabolism and genes that encode enzymes of relevant pathways or regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, focus on the latter has been largely motivated by the renewed interest in microalgae as biofuel feedstocks (Wijffels and Barbosa, 2010). As sequencing technology has become increasingly fast and affordable, comparison of transcriptomic changes under different experimental conditions by massive parallel sequencing of cDNA libraries is a viable first approach toward identifying genes that define changes in response to N deprivation or other nutrient stresses (González-Ballester et al, 2010). With the goal of gaining a better understanding of the factors underlying or even controlling the process of TAG accumulation following N deprivation, the focus has to be on metabolism and genes that encode enzymes of relevant pathways or regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, a number of microarrays have been used to interrogate changes in response to environmental factors (Ledford et al, 2004(Ledford et al, , 2007Jamers et al, 2006;Mus et al, 2007;Nguyen et al, 2008;Simon et al, 2008;Yamano et al, 2008;Mustroph et al, 2010). These microarrays could not cover all genes in the genome, but more recently, massively parallel cDNA sequencing approaches were applied to C. reinhardtii, overcoming the shortcomings of microarrays (González-Ballester et al, 2010). Likewise, we have chosen a cDNA sequencing-based approach using 454 and Illumina technologies in parallel that allow the generation of large numbers of ESTs of varying abundance, which can be counted to obtain a measure of gene expression (Weber et al, 2007).…”
mentioning
confidence: 99%
“…To further test this idea, RNA sequencing (RNA-seq) was used to determine genome-wide transcript abundance in the wild type and smt15-1 under sulfur-replete (+S) conditions or after 6 h in -S. Normally, SULFUR ACCLIMATION (SAC) genes are up-regulated to allow cells to cope with sulfur starvation stress (Zhang et al, 2004;González-Ballester et al, 2010). We found that the induction of SAC genes was either attenuated or decreased in smt15-1 (Table III).…”
Section: Smt15 Mrna Levels Are Light Regulatedmentioning
confidence: 99%
“…The synthetic genes can also be expressed in Phichia Pastoris or Escherichia coli to produce corresponding protein for biochemical studies. This technology could illuminate structural and regulatory gene networks to enlighten how plants reply to fast evolving hints and their environs (González-Ballester et al 2010).…”
mentioning
confidence: 99%
“…It allows access of the gene space of unsequenced recalcitrant species. Technological perfections in sequencing platforms; software and smart algorithms will further improve management and mining of large, repetitive plant genomes leading to understanding of plant biochemistry and physiology for application to crop improvement (Lohse et al 2012, Moerkercke et al 2013). …”
mentioning
confidence: 99%